Etnomathematics: exploration sanitary industry center of Malang - Intsani, Nadila Choirunnisa'; Mukti, Taufiq Satria; Rofiki, Imam (International Journal on Teaching and Learning Mathematics, 2022)
This study aims to explore the mathematical elements contained in the center of the sanitation industry in Malang City. The Sanitary Industry Setra is in the form of flower pots, gravestones, tombstones, fountains, hand washing stations, chairs, and so on. The object is an object of exploration based on an ethnomathematical point of view. This study uses a qualitative approach to the type of ethnographic research. The subjects in the study were sanitary ware craftsmen in the Karangbesuki area of Malang City. The subject is experienced and has a fairly large turnover. Data collection techniques in the study were carried out by observation or direct observation in the field, interviews, and also by studying literature. This research will provide evidence that without realizing it, people have applied the concepts of comparison, calculation and mathematical measurement in creating an object of crafts that have been carried out since ancient times. The mathematical implementation carried out by craftsmen produces crafts in the form of spatial geometric shapes such as: blocks, tubes, half balls, and others. In creating craft objects, researchers also found the concept result from geometric transformations such as: of translation, rotation, and also reflection on some of the crafts produced.